Alterations in HIV-1 gp120 V3 region are necessary but not sufficient for coreceptor switching in CRF07_BC in China. - Lei Zhang; Liying Ma; Zheng Wang; Yan Wang; Jing Zhang; Haining Wang; Yiming Shao (PLoS ONE)
The most predominant HIV-1 strains in China's current epidemic is the Circulating Recombinant Form 07_BC (CRF07_BC). CRF07_BC is mainly considered as a CCR5-tropic (R5) virus, since CXCR4-tropic (X4) viruses have thus far not been found in this subtype, and the molecular determinants of coreceptor switching remain unknown. To investigate the mechanisms underlying coreceptor requirement in CRF07_BC viruses, we characterized a panel of pNL4-3-based chimeric viruses with mutated V3 loop regions derived from an HIV-1 CRF07_BC infectious clone pXJDC13. Among 17 chimeric viruses, seven were dual-tropic and induced syncytium formation in MT-2 cells. Two amino acid insertions between positions 13 and 14, as well as arginine substitution at position 11 or 16 (IG insertion and P16R mutation or MG insertion and S11R mutation), conferred the chimeric viruses CXCR4-tropic features, which were same as subtype C X4 viruses. Next, to construct CRF07_BC X4 variants, mutated V3 loops were cloned into the CRF07_BC infectious clone pXJDC13. These V3 loops, which in the pNL4-3 backbone conferred chimeric viruses with CXCR4-using ability, abrogated infectivity completely in the CRF07_BC pXJDC13 genetic background. Similarly, IG insertion or MG insertion and S11R mutation dramatically diminished or completely abolished viral infectivity in other envelopes of subtype C or CRF07_BC. These results suggest that the effects of IG insertion and P16R mutation or MG insertion and S11R mutation on CXCR4 usage are context dependent, and additional mutations elsewhere in the envelope are needed to compensate for these fitness-reducing alterations.